Izraz MIR-21, HSP90 i GASP-1 u serumu pacijenata obolelih od raka pluća i njihova korelacija sa patološkim podtipovima: Serum miR-21, HSP90α, GASP-1 in Lung Cancer Subtypes - Pang, Hongyan; Gong, Yange; Wang, Yaojie; Zhang, Lianyong (Journal of Medical Biochemistry, 2024)
Background: To investigate the expression of miR-21, heat shock protein-90α (HSP90α) and G protein-coupled receptor-related sorting protein 1(GASP-1) in the serum of lung cancer patients and their correlation with pathological subtypes. Methods: Eighty patients with lung cancer were included in the lung cancer group from May 2020 to May 2022, and 40 volunteers who underwent physical examination were randomly included in the control group according to the group ratio of 2:1. Serum miR-21, HSP90α and GASP-1 levels of patients in the two groups were detected. To explore the correlation between it and pathological subtypes, TNM stage and lymph node metastasis of lung cancer patients. Results: The serum levels of miR-21, HSP90α and GASP-1 in lung cancer group were higher than those in control group (P < 0.05). ROC curve analysis showed that serum miR-21, HSP90α and GASP-1 levels had certain value in the diagnosis of lung cancer, and their AUC values were 0.901, 0.874 and 0.865, respectively (P < 0.05). There was no difference in the relative expression level of serum miR-21 between squamous cell carcinoma group and adenocarcinoma group (P>0.05), but the levels of HSP90α and GASP-1 in adenocarcinoma group were higher than those in squamous cell carcinoma group (P < 0.05). There was no difference in the levels of serum miR-21, HSP90α and GASP-1 between stage I and stage II groups (P>0.05). The levels of serum miR-21, HSP90α and GASP-1 in stage III and stage IV groups were higher than those in stage I and stage II groups, and those in stage IV were higher than those in stage III group (P < 0.05). The serum levels of miR-21, HSP90α and GASP-1 in patients with metastasis were higher than those in patients without metastasis (P < 0.05). Conclusions: In patients with lung cancer, serum miR-21, HSP90α and GASP-1 levels were increased, which were associated with pathological subtypes, stage and lymph node metastasis, and had high diagnostic significance in the clinic.